Quantum Dynamics of Rotational Transitions in CN (X2Σ+) by H+ Collisions - Anusuri, Bhargava; Dhilip Kumar, T. J.; Kumar, Sanjay (Frontiers in Chemistry, 2021)
Collisional cross-sections of inelastic rotational excitations of CN in its ground electronic state (X2Σ+) by H+ scattering are studied by the exact quantum mechanical close-coupling (CC) method at very low collision energies (0–600 cm−1) relevant to interstellar atmospheres. Ab initio rigid rotor potential energy surface computed at MRCI/cc-pVTZ level of accuracy has been employed. Rate coefficients for the rotational excitations have also been calculated. The obtained results are compared with previous theoretical calculations and analyzed whether proton collisions could be significant sources for rotationally excited CN as a possible source for cosmic microwave background of about 3 K from the interstellar media.